Assessment of the improved cooling effectiveness of modified film holes supplied by the front cavity on a vane - Fei Zeng; Lin Ye; Yang Li; Wei Li; Cunliang Liu; Fan Zhang (Case Studies in Thermal Engineering, 2025)
Vanes are generally supplied with coolant through multiple cavities. Improving film holes supplied by the front cavity can impact the overall film coverage on the vane. In this study, the deficiencies of the film cooling characteristics were analyzed. This study aimed to increase the number of film holes supplied by the front cavity of a vane, and two improved models (Vanes I and II) were proposed. The holes on the suction side were improved to 11–11–11 holes in the improved models. The showerhead hole diameter on Vane I increased by 25 %. The showerhead holes on Vane II were changed to laidback holes. The most upstream holes on the pressure surface of both improved models were changed to 11–11–11 holes. The enhanced effective cooling of the improved models under different mass flux ratios and turbulence intensities was evaluated. Compared with the original vane, Vanes I and II exhibited significantly improved effective film cooling on the showerhead and suction surfaces. The amount of film cooling also increased on the pressure surface near the showerhead. This improvement gradually decreased along the flow direction. Under different mainstream parameters, the effective film cooling rates of Vanes I and II both increased by more than 32 %. Moreover, Vane II was more resistant to turbulence intensities and mass flux ratios.